A Comparative Study of Morphometric Profiles and Hematological Analysis and Food Preference Between Male and Female Spotted Redshank (Tringa erythropus) Sampled from Different Wetlands of Punjab, Pakistan - Shabbir Ahmad; Hasnain Akmal; Kamran Jafar (RADS Journal of Biological Research & Applied Science, 2023)
Background: Spotted redshank (Tringa erythropus) is a shorebird. Morphometric and feeding studies on birds were very important to understanding geographic distribution and it plays a key role in conservation of particular species.